1992
DOI: 10.1002/1097-0142(19920315)69:6<1513::aid-cncr2820690633>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoma. Treatment results and conversion to myeloma

Abstract: Forty‐six cases of solitary plasmacytoma were reviewed for response to radiation and progression to multiple myeloma. Cases were classified as solitary plasmacytomas of bone (SPB) (32 cases) or extramedullary plasmacytomas (EP) (14 cases). There was an overall 93% response rate of the tumor to radiation therapy: 62% had a complete response after radiation therapy, whereas 31% had a partial response. Conversion to multiple myeloma was influenced by the type of plasmacytoma; 53% of the patients with SPB converti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
214
7
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(245 citation statements)
references
References 21 publications
12
214
7
9
Order By: Relevance
“…Compared to other studies, the median time to progression of 34.3 months we saw in our patients forms the upper end of the reported range of 13 -36 months [1,7,8,9]. Six out of nine patients with progressive disease developed multiple myeloma in the first year after diagnosis.…”
Section: Progression To Multiple Myelomacontrasting
confidence: 62%
See 1 more Smart Citation
“…Compared to other studies, the median time to progression of 34.3 months we saw in our patients forms the upper end of the reported range of 13 -36 months [1,7,8,9]. Six out of nine patients with progressive disease developed multiple myeloma in the first year after diagnosis.…”
Section: Progression To Multiple Myelomacontrasting
confidence: 62%
“…For EP, significantly better local control was reported for doses >45 Gy (100% 5-year LCR vs. 55% for <45 Gy) [15]. Considering the low treatment toxicity, doses of 40-50 Gy seem to be a general consensus for SBP [1,12,16] and of 40-60…”
Section: Influence Of Dosementioning
confidence: 97%
“…Reported by Huang et al, in patients with SP of cervical spine, adjunctive RT following excision obviously decreased MM progression (Huang et al, 2010). Another retrospective study showed favorable effects related to melphalan-based chemotherapy in preventing MM development (Mayr et al, 1990), but others didn't report any benefits of chemotherapy (Holland et al, 1992;Katodritou et al, 2014). Unfortunately, our study doesn't have the potency to explore the effectiveness of intensive therapy in patients of high risk owing to the small number of events.…”
Section: Discussionmentioning
confidence: 77%
“…Primary extramedullary plasmacytomas are also rare, and they commonly originate in head and neck, especially in the upper aerodigestive tract [4,5]. Extraosseous spread was found in approximately two-thirds of the myeloma patients at autopsy [2,6].…”
Section: Discussionmentioning
confidence: 99%